Violência psicológica entre parceiros íntimos na juventude: da invisibilidade à compreensão - Ferreira, Isabel Bernardes (2024)
If for a long time physical violence against women was naturalized, in contemporary times we see psychological violence being trivialized and invisible in the eyes of society. Psychological violence is present in other expressions of violence, but it is also violence of a specific nature that keeps women and men absorbed in unhealthy relationships, with low satisfaction and generating psychological and physical illnesses. The literature points out that such violence is a phenomenon with a high incidence in informal relationships, such as dating, and among the population of adolescents and young adults. In view of the above, the need for further research on intimate and committed relationships was assessed, as well as on psychological violence in intimate partnerships among the population of adolescents and young adults aged 15 to 24, a period that encompasses youth and refers to those who were born in the digital age. To this end, two literature reviews were carried out, a Scope Review and another State of the Issue Review, which contributed to the organization of a documentary study through the netnography procedure on the social media Instagram and TikTok. The results of the study are distributed across four articles. From this Thesis it was possible to confirm the literature in terms of recognizing and identifying the attitudes that make up psychological violence in an intimate relationship, evaluating its consequences that involve behaviors that cause mental confusion, emotional dependence and feelings of devaluation. It is also worth highlighting how documentary research allowed access to content that, on the one hand, is positive as an investigation strategy, and on the other, refers to psychological processes that support the naturalization and trivialization of violence